PERANCANGAN PROTOTIPE SISTEM TRACEABILITY AKTIVITAS PRODUKSI PADA INDUSTRI JAMUR PT GAYA GREEN SRIKANDI - Syarif, Ahmad
PT Gaya Green Srikandi, a company engaged in oyster mushroom cultivation, currently faces challenges in maintaining consistent production and achieving optimal yields. This is due to the absence of a structured system for tracking and tracing the production parameters employed. To address this issue, this research proposes the design of a traceability system utilizing Internet of Things (IoT) and QR code technology to collect data specific to each baglog batch. Previous research has designed an IoT-based monitoring system used in several stages of the production process. However, the data obtained from this monitoring system has not been fully utilized because the information gathered does not directly correlate with the goods being produced. As a result, the monitoring system data cannot be used to determine the cause of higher defect rates in certain batches compared to others. This research will generate four main outputs: microcontroller connection programming code, a database system, a user interface for data logging, and programming code to integrate these three components. Simulation testing demonstrates that the system can monitor the location of a batch at various stages of the production process. Additionally, the data stored in the system allows for tracing the specific production processes undergone by a particular batch. This indicates that the designed traceability system can serve as a comprehensive monitoring tool for PT Gaya Green Srikandi, potentially leading to improved yield, reduced defects, and enhanced process efficiency.